Sharing of ADHD Information between Parents and Teachers Using an EHR-Linked Application - Michel, Jeremy J.; Mayne, Stephanie; Grundmeier, Robert W.; Guevara, James P.; Blum, Nathan J.; Power, Thomas J.; Coffin, Emily; Miller, Jeffrey M.; Fiks, Alexander G. (Applied Clinical Informatics, 2018)
Background Appropriate management of attention-deficit/hyperactivity disorder (ADHD) involves parents, clinicians, and teachers. Fragmentation of interventions between different settings can lead to suboptimal care and outcomes. Electronic systems can bridge gaps across settings. Our institution developed an email-based software to collect ADHD information from parents and teachers, which delivered data directly to the clinician within the electronic health record (EHR).Objective We sought to adapt our institution's existing EHR-linked system for ADHD symptom monitoring to support communication between parents and teachers and then to assess child characteristics associated with sharing of ADHD information.Methods We updated our software to support automated sharing of ADHD information between parents and teachers. Sharing was optional for parents but obligatory for teachers. We conducted a retrospective cohort study involving 590 patients at 31 primary care sites to evaluate a system for sharing of ADHD-specific health information between parents and teachers. We used multivariable logistic regression to estimate associations between child characteristics and parental sharing. We further investigated the association between child characteristics and viewing of survey results delivered through the electronic communication system.Results Most parents (64%) elected to share survey results with teachers at the first opportunity and the vast majority (80%) elected to share all possible information. Parents who elected to share usually continue sharing at subsequent opportunities (89%). Younger child age and performance impairments were associated with increased likelihood of sharing. However, parents viewed only 16% of teacher submitted surveys and teachers only viewed 30% of surveys shared by parents.Conclusion This study demonstrates that electronic systems to capture ADHD information from parents and teachers can be adapted to support communication between them, and that parents are amenable to sharing ADHD information with teachers. However, strategies are needed to encourage viewing of shared information.
Keywords: attention-deficit/hyperactivity disorder; information dissemination; surveys and questionnaires; communications; other clinical informatics applications